A CONCEPTUAL FRAMEWORK FOR SUPERIOR HIGH-QUALITY HUMAN CAPITAL IN THE ACCOUNTING PROFESSION - Ranita Puspita Sari Dewi; Laili Fauziah; Sigit Mareta; Kup Yanto Setiono; Caturida Meiwanto Doktoralina (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
Strengthening the accounting profession to support the Golden Indonesia 2045 vision requires improving the quality of human resources to respond to the acceleration of technological transformation, the development of international professional standards, and the increasing demands for ethical accountability. Human capital theory has emphasised that investments in education, experience, and professional development enhance individual and organisational performance, yet the integration of human resource theory into accounting studies that project future competency needs remains limited. Therefore, this conceptual study develops a framework for a model of human resource excellence relevant to the accounting profession. This research employs a qualitative approach using a literature review method by analysing relevant scientific literature. The data were analysed using a descriptive qualitative approach through theoretical synthesis and content analysis. This conceptual study place technical accounting competency, digital literacy, and ethical judgement as key domains shaping professionalism in a knowledge-based economy. The framework integrates Werther and Davis's competency theory to explain the interaction between knowledge, skills, and behaviour in producing superior and competitive human resources. A human resource accounting perspective further strengthens this approach by recognising employees as strategic organisational assets that create sustainable value. The synthesis of various theoretical perspectives produces a conceptual model that can serve as a basis for developing accounting education curricula, professional development policies, and an empirical research agenda to strengthen the capacity of Indonesian accountants to face global economic dynamics.